Green synthesis of magnetic sodalite sphere by using groundwater treatment sludge for tetracycline adsorption. (20th February 2020) - Zhu, Suiyi; Wu, Yaqiong; Qu, Zhan; Zhang, Leilei; Yu, Yang; Xie, Xinfeng; Huo, Mingxin; Yang, Jiakuan; Bian, Dejun; Zhang, Haifeng; Zhang, Lanhe
Abstract: Herein, a green approach was developed to recycle groundwater treatment sludge effectively for preparing magnetic sodalite adsorbent (MS) via a one-step alkali hydrothermal route without the addition of exogenous Si/Al sources. The groundwater treatment sludge was a typical solid waste composed of ferrihydrite, boehmite and quartz, and weakly magnetized in its irregular form. After a hydrothermal treatment of 3 M NaOH, ferrihydrite in the sludge was transformed into hematite, with magnetic maghemite as an intermediate. Boehmite and quartz were dissolved under alkaline conditions and recrystallized on the Fe oxide surface to form a sodalite spherical coating. The product prepared at 3 M NaOH was MS3, which had fine spherical particles with diameters between 3 and 5 μm and exhibited a saturation magnetization of 10.4 emu/g. Increasing the NaOH concentration could improve the saturation magnetization of the prepared magnetic adsorbent but could destroy the sodalite sphere. MS3 exhibited a high tetracycline (TC) adsorption capacity of 488.1 mg/g. The adsorption data fitted well with the pseudo-second-order model, whereas the adsorption isotherm fitted well with the Langmuir model. The major adsorption mechanism was the coordination reaction between the –NH2 group on the side chain of a TC molecule and the H atom of the hydroxyl groups on the sodalite surface. This study not only developed a novel and useful method for effectively recycling groundwater treatment sludge but also presented the potential of the prepared magnetic sodalite sphere for application in wastewater treatment. Graphical abstract: Image 1 Highlights: Low Si/Al-containing sludge was directly converted into magnetic sodalite sphere. The sphere had Fe oxides core covered with sodalite shell. High NaOH concentration improved the sphere magnetization. The sphere was efficient in tetracycline adsorption.